2016
DOI: 10.1088/1752-7155/10/2/026002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolomics panels for potential lung cancer screening by analysis of exhaled breath condensate

Abstract: Exhaled breath condensate (EBC) is one of the less employed biofluids when searching for clinical markers, despite its non-invasive sampling and the potential relationship between its composition and respiratory disease phenotypes such as lung cancer. The advanced stage at which lung cancer is usually detected is the main reason for the high mortality rate of this carcinogenic disease. In this preliminary research, EBC was used as clinical sample to develop a screening tool for lung cancer discrimination from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…We also compared LC with benign nodules, with results similar to those from previous studies. 13,14,19,20,26,27 In our previous pilot study of patients from Colorado, we showed that benign pulmonary nodules could be well discriminated from LC by a unique breath print. 25 The nanoarray sensors could also discriminate between adenocarcinomas and SCCs and between early-stage and advanced disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We also compared LC with benign nodules, with results similar to those from previous studies. 13,14,19,20,26,27 In our previous pilot study of patients from Colorado, we showed that benign pulmonary nodules could be well discriminated from LC by a unique breath print. 25 The nanoarray sensors could also discriminate between adenocarcinomas and SCCs and between early-stage and advanced disease.…”
Section: Discussionmentioning
confidence: 89%
“…In another interesting study performed by Peralbo-Molina et al, five different metabolites (monopalmitin, benzyl alcohol, monostearin, 2,4-diphenyl-4-methyl-2-E-pentene, and p-cresol) were used to form three panels. 27 Patients with LC were differentiated from healthy controls and patients with risk factors with a sensitivity higher than 77.9%, a specificity higher than 67.5% and an area under the curve higher than 77.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Breath metabolomics has also shown promising results for detecting colon cancer, breast cancer, infectious disease, asthma, and others. (19)(20)(21)(22)(23)(24)(25) Here, we present a model developed from breathbased metabolites (volatile organic compounds [VOCs]) to classify patients as being healthy, having pulmonary hypertension (as a disease control), cirrhosis, HCC, or CRLM in a large and well-characterized cohort of patients with liver disease. We compare and contrast our model's prediction accuracy for detecting HCC to the current clinical standard, AFP, and examine the potential for breath metabolomics as a noninvasive screening tool for detecting liver diseases.…”
mentioning
confidence: 99%
“…The proposed combination model has been demonstrated to be advantageous for predicting the outcome in patients with aneurysmal subarachnoid haemorrhage [ 22 ] and prognosis in severe traumatic brain injury [ 23 ]. Also, it has been applied to discriminate between patients with lung cancer versus smokers [ 24 , 25 ]. In a previous work, we reported the high values of MIP-1b and adipsin in patients with ALS [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%